Statins: have we found the Holy Grail? (Swiss Medical Weekly, 2012)
In coronary artery disease, cardiovascular risk factors are the main targets for primary and secondary prevention. Statins prevent cardiovascular events in patients at risk. However, despite the proven efficacy and safety of statins, relevant side effects exist and should be considered when treating patients.